Videoconferencing Software Options for Telemedicine: A Review for Movement Disorder Neurologists - Cubo, Esther; Arnaiz-Rodriguez, Adrian; Arnaiz-González, Álvar; Díez-Pastor, José Francisco; Spindler, Meredith; Cardozo, Adriana; Garcia-Bustillo, Alvaro; Mari, Zoltan; Bloem, Bastiaan R. (Frontiers in Neurology, 2021)
Background: The use of telemedicine has increased to address the ongoing healthcare needs of patients with movement disorders. Objective: We aimed to describe the technical and basic security features of the most popular telemedicine videoconferencing software. Methods: We conducted a systematic review of articles/websites about “Telemedicine”, “Cybersecurity”, and “Videoconferencing software”. Technical capabilities and basic security features were determined for each videoconferencing software. Results: Twenty-six videoconferencing software programs were reviewed, 13 (50.0%) were specifically designed for use in healthcare, and 6/26 (23.0%) were compliant with both European and US regulations. Overall technical and security information were found in 5/26 software (19.2%), including Microsoft Teams, Google Hangout, Coviu, Doxy.me and Thera platforms. Conclusions: Detailed information about technical capabilities and data security of videoconferencing tools is not easily and openly retrievable. Our data serves as a guide for practitioners seeking to understand what features should be examined when choosing software, and what options are available.